Evaluation of Gonad Reproductive Condition Using Non-invasive Ultrasonography in Red Abalone (Haliotis rufescens) - Boles, Sara E.; Neylan, Isabelle P.; Rogers-Bennett, Laura; Gross, Jackson A. (Frontiers in Marine Science, 2022)
Reproductive status in abalone (Haliotis spp.) can be difficult to discern using traditional visual inspection and may therefore rely on lethal histological analyses for definitive determination. With endangered species of abalone, lethal histological examinations are strictly prohibited. Here, we investigated the effectiveness of non-invasive ultrasonography as an alternate means of identifying the reproductive status of abalone rather than histology methods. We examined twelve red abalone produced at an aquaculture farm to test our methods. We found that ultrasound technology effectively differentiates between reproductive and digestive tissues allowing for accurate characterization of an ultrasound gonad index score. Following our initial gonad ultrasound determination, we monitored 100, five year old, red abalone using ultrasonography to detect changes in gonad size for seven weeks. Abalone were then spawned and gonads were also evaluated immediately post spawning. We found that ultrasound technology was successful in rendering a gonad index score which can be used not only in endangered species but also allows us to track the development of the reproductive tissue over time. Tracking gonad scores over time can be useful for improving abalone production by increasing animal welfare by reducing handling stress associated with gonad assessments and then selecting individual abalone that are empirically determined ready to be spawned. Non-invasive ultrasound technology has the potential for broad applications within abalone aquaculture to enhance both food and conservation breeding programs.